Evaluating the residual life of aged railway bridges. Issue 4 (5th June 2019) - Mansell, Bruce; Ngamkhanong, Chayut; Kaewunruen, Sakdirat
Abstract : The UK is home to a very expansive railway network. The network includes a significant number of bridges that were constructed in the Victorian era. The aim of this study is to estimate the remaining lifespan of a unique aged railway bridge, the Windsor Railway Bridge in the UK. This research encompassed several steps: analysis of past and current traffic, prediction of future traffic trends, fatigue life analysis, estimation of lifespan consumption and estimation of remaining fatigue life. The finite-element analysis results showed that the most highly stressed members in the structure were the arch stringer and arch vertical bracing. By using the finite-element method together with the cumulative fatigue theory, these members are predicted to have failed in 5–7 years' time, depending on the future traffic trends. Under a less conservative design class, some members are shown to have already failed sometime in the 1920s. It is found that a number of major conservative design assumptions were made. The failure mode and mechanism of the aged railway bridge are highlighted in this paper.